2010
DOI: 10.1007/978-3-642-13431-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles for the PIP Family of Plant Aquaporins

Abstract: Aquaporins are a class of intrinsic membrane proteins that are primarily associated with water movement across membranes. In plants, biophysical studies indicated that water fluxes could not be explained by simple diffusive movement. The discovery of aquaporins that facilitate water movement across membranes in other organisms rapidly led to the identification of this class of proteins in plants. The large number of aquaporin genes identified in plant genomes compared to those from other organisms suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 169 publications
(250 reference statements)
0
2
0
Order By: Relevance
“…35 Also, it has been found that AQPs can serve as ion-selective transporters to mediate the transport of other small molecules, nutrients, and metal ions. 36 TIPs (tonoplast intrinsic proteins) and PIPs (plasma membrane intrinsic belong to different subfamilies of AQPs. It has been reported that the growth of C. rietinum plants was promoted by carbon nanotubes by enhancing their capacity to absorb and reserve water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Also, it has been found that AQPs can serve as ion-selective transporters to mediate the transport of other small molecules, nutrients, and metal ions. 36 TIPs (tonoplast intrinsic proteins) and PIPs (plasma membrane intrinsic belong to different subfamilies of AQPs. It has been reported that the growth of C. rietinum plants was promoted by carbon nanotubes by enhancing their capacity to absorb and reserve water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Plant aquaporins (AQPs) are multifunctional plant cell membrane proteins that can transport the water, gases, and nutrients, regulating flowering, stomatal movement, reproductive growth, and response to various stresses . Also, it has been found that AQPs can serve as ion-selective transporters to mediate the transport of other small molecules, nutrients, and metal ions . TIPs (tonoplast intrinsic proteins) and PIPs (plasma membrane intrinsic proteins) belong to different subfamilies of AQPs.…”
Section: Resultsmentioning
confidence: 99%